Boron carbide, B13-xC2-y (x = 0.12, y = 0.01) - Sologub, Oksana; Michiue, Yuichi; Mori, Takao (Acta crystallographica. Section E, Structure reports online, 2012)
Boron carbide phases exist over a widely varying compositional range B 12+ x C 3- x (0.06 < x < 1.7). One idealized structure corresponds to the B 13 C 2 composition (space group R -3 m ) and contains one icosahedral B 12 unit and one linear C—B—C chain. The B 12 units are composed of crystallographically distinct B atoms B P (polar, B1) and B Eq (equatorial, B2). Boron icosahedra are interconnected by C atoms via their B Eq atoms, forming layers parallel to (001), while the B 12 units of the adjacent layers are linked through intericosahedral B P —B P bonds. The unique B atom (B C ) connects the two C atoms of adjacent layers, forming a C—B—C chain along [001]. Depending on the carbon concentration, the carbon and B P sites exhibit mixed B/C occupancies to varying degrees; besides, the B C site shows partial occupancy. The decrease in carbon content was reported to be realized via an increasing number of chainless unit cells. On the basis of X-ray single-crystal refinement, we have concluded that the unit cell of the given boron-rich crystal contains following structural units: [B 12 ] and [B 11 C] icosahedra (about 96 and 4%, respectively) and C—B—C chains (87%). Besides, there is a fraction of unit cells (13%) with the B atom located against the triangular face of a neighboring icosahedron formed by B Eq (B2) thus rendering the formula B 0.87 (B 0.98 C 0.02 ) 12 (B 0.13 C 0.87 ) 2 for the current boron carbide crystal.